Governance reform and IPO underpricing - Ekkayokkaya, Manapol; Pengniti, Tulaya (Journal of Corporate Finance, 2012)
Underpricing of IPOs in Thailand significantly drops following the country's major governance reform, indicating less price-protection by investors. The lower price-protection is associated with fewer instances of absolute control retention by pre-issue insiders during the post-reform period, not reduction in the expropriation risk. While corporate disclosure does not reveal issuers' true risk type before the reform, it does so after the reform. Yet, insiders make significantly less disclosure when retaining absolute control regardless of the reform. We conclude that governance regulation in an economy with fundamentally weak legal institutions works, but its efficacy is limited when insiders retain absolute control.